KESIAPAN MASYARAKAT TERHADAP PEMBANGUNAN HUTAN KEMASYARAKATAN DI DESA KILO POSO PESISIR UTARA - Possumah, Inggrid Margareth; Golar, Golar; Toknok, Bau (Universitas Tadulako, 2015)
Social Forestry is a state Forest which is primarily indicated to empower local communities. The goal of Social Forestry was to improve the public welfare around the forest, by providing greater access to the public to be able to harness the area of the forest in order to increase their income and quality of life. The development of Social Forestry have to be considered, starting from back-up working area of Social Forestry, the preparation conditions of the community, the formation of Social Forestry up to the establishment of monitoring and evaluation in the field. This research was aimed to determine the perceptions and attitudes of the community towards the development of Social Forestry such us community preparedness, biophysical, economic and the institutions. This research applied descriptive method through primary and secondary data, while data analysis which is used was 1-3-5 scale (Likert Scale Modified). The result showed the perceptions and attitudes of Kilo village towards the developing of Social Forestry plan is low, showed by a score(82). There are two factors that causes the understanding of society classified as very low or weak like education and socialization factors. Human resources in this village is very limited caused by on the average, people only took primary school education while the reason that causes lack of socialization is the limitation of the KPH. Different from the community of Kilo, they already well prepared and enthusiastic in welcoming the development of Social Forestry plan in their village was very high showed by a score (192) although their understanding about Social Forestry very low. Keywords : Preparation and Attitude, The Readiness of Biophysical, The Readiness of Agencies, The Readiness of Institutions.